Global research hot spot and trends in tinnitus treatment between 2000 and 2021: A bibliometric and visualized study - Ye, Tao; Chen, Kefan; Li, Dongyang; Yin, Kailong; Li, Yuan; Long, Jin; Hui, Lian (Frontiers in Neurology, 2023)
Background In the 21st century, the prevalence of tinnitus is increasing, impacting approximately one in five people. It is a very complicated condition that significantly affects quality of life. Despite the availability of hundreds of tinnitus treatment options, none are very successful. In light of this, there has been a steady increase in studies on tinnitus treatments in the recent past. To comprehend them better, this study used bibliometric approaches to analyze and summarize 21st century scientific research accomplishments in tinnitus treatment. Methods The Web of Science Core Collection (WoSCC) was searched for papers that had been published and related to the treatment of tinnitus. VOSviewer, CiteSpace, R, and Tableau software programs were used to conduct bibliometric studies. To evaluate and visualize the results. Results 2,933 publications on tinnitus treatment were found in 74 countries. Between 2000 and 2021, publications increased steadily. Otolaryngology-Head & Neck Surgery had the highest impact factor, whereas Otology & Neurotology had the most magazines and the highest h, g, and m index. Langguth B was the most prolific author in terms of productivity during the past 21 years. Numerous eminent authors and organizations from multiple nations collaborated. With 626 papers, the United States of America (USA) contributed the most to this field, making them the leading contributor. Neuroplasticity, sound therapy, and cognitive behavioral therapy (CBT) have attracted the attention of researchers, leading to the development of innovative diagnostic and treatment strategies for tinnitus. Conclusion This bibliometric study provides a comprehensive analysis of worldwide publications, cooperation, and research hotspots in tinnitus therapy, revealing the present status of research on this issue and guiding tinnitus treatment research in the coming years.